CURRENT ASPECTS OF FORMATION IN STUDENTS HEALTHY LIFESTYLE - T.H. Trofanova (Academy of Cognitive and Natural Sciences, 2022)
In the article look at actual aspects increase level of health for children and have owning habits and skill of health life.